Image-potential states on bcc (110) surfaces of iron and tungsten - Thomann, Ulrich; Reuss, Christian; Fauster, Thomas; et al. (Physical Review B, 2000)
Image-potential states have been measured for W(110) and for bce Fe(110) films on W(110) and Cu(100) substrates. Energies and linewidths are reported and for the W(110) substrate an unusually small effective mass of 0.5m(e) is found. For Fe(110), the majority and minority spin contributions were separated using polarization-dependent two-photon photoemission without magnetizing the sample.